52 Decisions about cardiopulmonary resuscitation in patients receiving specialist palliative care: a multi-centre regional audit of practice. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Roberts, Joanna; McDonald, Rachel; Cadwallader, Claire; Marley, Kate; Smith, Jenny; Coyle, Seamus; Gratwick, Kate; Thompson, Anthony
Abstract : Background: When performed inappropriately cardiopulmonary resuscitation (CPR) can prevent those with irreversible illness having a peaceful death. In people approaching the end of life, making decisions about whether to attempt CPR is integral to good care. Aim: Audit clinical practice around CPR decision–making and communication with patient's, those important to them and other healthcare professionals (HCPs) against regional standards. Use audit outcomes to update regional standards and guidelines. Methods: Systematic literature review examining education for HCPs, communication with patients and those important to them and dissemination of decisions Survey of HCPs working in specialist palliative care Multi–centre retrospective case note review of patients with a do not attempt cardiopulmonary resuscitation (DNACPR) decision receiving specialist palliative care in hospital, hospice or community settings. Results: 73 HCP's participated in the survey and 87% had discussions about CPR. In HCPs having conversations about CPR 75% rated their confidence in doing so as 8/10 or higher. 187 case notes were reviewed. While DNACPR forms indicated whether the decision had been discussed with the patient in 87% only 72% had a record of this in the written notes. 68% of case notes had a record of discussions or reasons for non-discussion with those important to the patient. 34% of patients moved care setting after the DNACPR decision, of these 64% transferred with a unified DNACPR form. Conclusion: This audit shows ongoing challenges in communicating with patients and those important to them about CPR. Improvement is required in disseminating DNACPR decisions when patients transfer care settings.